Stimulatory Effects of Different Seed Priming Treatments on Germination and Early Seedling Growth of Sugar Beet - Nilüfer KOÇAK ŞAHİN (ISPEC Journal of Agricultural Sciences)
As known, seed germination constitutes the first stage in plant production, and the rapidness of this trait is important for the agriculture of the sugar beet. Particularly, it is crucial to realize after the winter and cool weather. The main aim of the study was to accelerate seedling growth by germinating them observe their effects on plant emergence, and improve seed viability using Serenada, Aranka, and Lider sugar beet varieties treated with hydropriming, hormonal priming, and organic priming for 6, 12, and 18 h under room temperature and humidity conditions. The study showed that the behavior of treated seeds was significantly different compared to the control treatment. The germination percentage, mean germination time, shoot length and root length     ranged between 85.50-95.00 (%), 2.80-4.49 (days), 6.34-9.82 (cm), and 3.73-9.12 (cm) respectively. Seedling fresh and dry weight changed between 57.88-89.66 (mg plant-1), and 5.02-12.31 (mg plant-1) in the same order. The best results in germination percentage, mean germination time, root length, and maximum seedling dry weight were obtained after seaweed treatments for 18 h, for seedling length seedling fresh weight. It is concluded that growth parameters are genotype-dependent. Used genotypes in this experiment showed different responses for the investigated agronomic characters (with the priming treatments), and they can be used in any local sugar beet programs for the investigated traits with a carefully selected depending on the objectives of the study.